A PC / ABS alloy material and preparation method thereof
By using a composite flame retardant system and a high-flow matrix in PC/ABS alloy materials, the problems of material flammability, heat resistance and impact strength are solved, and the effects of halogenation-free, good flame retardant performance and superior appearance performance are achieved.
Patent Information
- Application Number
- CN202411520566.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing PC/ABS alloy materials are prone to produce harmful gases and smoke during combustion, and the high amount of halogen-free flame retardant added leads to a decrease in heat resistance and impact strength, and there is room for improvement in appearance.
Through the composite raw material ratio and preparation steps, medium and low viscosity polycarbonate, ABS high glue powder and ultra-high flow grade acrylonitrile-styrene copolymers are used to form a high flow matrix, combining phosphate, silicone and sulfonate flame retardant, as well as ultrafine barium sulfate to form a composite flame retardant system, improving the flame retardant and heat resistance of the material, while maintaining high impact strength and gloss.
The halogenation-free PC/ABS alloy material has good flame retardant properties, heat resistance and high impact strength, and has better appearance performance, overcoming the performance degradation caused by traditional halogen-free flame retardants.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PC composite materials, and in particular to a PC / ABS alloy material and a preparation method thereof. Background Art
[0002] PC / ABS alloy material combines the excellent properties of ABS and PC. It is a polymer alloy with comprehensive performance. It can be sprayed on the surface of home appliance housings, automotive interior and exterior decoration and other products to improve the appearance. However, PC / ABS alloy material has the disadvantage of being easy to burn and produces a large amount of harmful gases and smoke when burning. The fire hazard caused by this has become the focus of attention. Flame retardants are usually added to make PC / ABS alloy materials flame retardant, self-extinguishing and smoke-extinguishing. Halogen flame retardants have a large amount of smoke and release hydrogen halide gas when burning. They easily absorb water to form highly corrosive hydrohalic acid and cause secondary pollution. Therefore, halogen-free has become a new trend. However, the traditional halogen-free phosphate system flame retardant has a high addition amount, which has a defect that the heat resistance and impact strength are significantly reduced due to the large damage to the intermolecular bonding of polycarbonate. Secondly, the glossiness of the common PC / ABS alloy materials on the market is average, and there is still room for improvement in appearance. Summary of the invention
[0003] The main purpose of the present invention is to provide a PC / ABS alloy material and a preparation method thereof. Through a composite raw material ratio and preparation steps, a PC / ABS alloy material with high gloss, good heat resistance and less impact strength reduction is obtained, which overcomes the technical defects of the halogen-free PC / ABS alloy material in the background technology that the impact strength and heat resistance of the halogen-free PC / ABS alloy material are significantly reduced and there is still room for improvement in the appearance effect.
[0004] To achieve the above object, the present invention provides a PC / ABS alloy material and a preparation method thereof, wherein the raw material formula comprises the following components in parts by weight:
[0005] Polycarbonate (PC): 70-78 parts;
[0006] Acrylonitrile-styrene copolymer (AS for short): 8-10 parts;
[0007] ABS high glue powder: 3-6 parts;
[0008] Sulfonate flame retardant: 0.1-0.3 parts;
[0009] Silicone flame retardant: 1-3 parts;
[0010] Phosphate flame retardant: 3-6 parts;
[0011] Superfine barium sulfate: 1-3 parts;
[0012] Processing aids: 1.0-1.5 parts;
[0013] Polycarbonate, under the test conditions of 300℃ and 1.2KG, has a melt index of 15-25; acrylonitrile-styrene copolymer, under the test conditions of 220℃ and 10KG, has a melt index of 45-60;
[0014] The mesh number of the ultrafine barium sulfate is 1250 mesh to 5000 mesh, and the purity is above 98%.
[0015] The invention discloses an ABS with good fluidity which is prepared by mixing acrylonitrile-styrene copolymer and ABS high-rubber powder, and combines it with medium-low viscosity polycarbonate to form a matrix with good fluidity, uses phosphate flame retardant and organosilicon flame retardant to form a composite flame retardant system, and adds sulfonate flame retardant and ultrafine barium sulfate as synergists of the composite flame retardant system, thereby making up for the defects of a high addition amount of flame retardant in a traditional phosphate system, which greatly damages the bonding between polycarbonate molecules and leads to decreased impact strength and poor heat resistance.
[0016] Through the above compounding, the metaphosphoric acid produced by the phosphate flame retardant during the combustion and decomposition stage of the polymer promotes the dehydration and carbonization of the polymer, and forms a first carbon layer on the surface of the polymer to insulate and isolate oxygen, thereby preventing the polymer from continuing to burn. The sulfonate flame retardant is compounded with the silicone flame retardant to generate an inorganic oxygen-insulating and heat-insulating protective carbon layer containing Si bonds or Si-C bonds unique to polysiloxane when the material burns, which can improve the oxidation resistance of the first carbon layer, prevent the escape of combustion and decomposition products, and inhibit the thermal decomposition of the material again, thereby improving the safety of the material use. The ultrafine barium sulfate has stable chemical properties and is difficult to burn. It absorbs heat and decomposes in a high-temperature flame environment to produce sulfuric acid and barium oxide, which can quickly consume the heat of the material.
[0017] The composite flame retardant system has the problems of complex components, large differences in addition ratios, and large differences in particle morphology with the matrix material. When the matrix has insufficient fluidity, it is difficult to form a good combination with the composite flame retardant system, which affects the composite flame retardant system from playing a good flame retardant synergistic role. This solution makes the composite flame retardant system play a better flame retardant synergistic role by combining a matrix with good fluidity with the composite flame retardant system, and reduces defects such as pinholes and pitting on the surface of the alloy material. Therefore, the prepared PC / ABS alloy material not only has the characteristics of being halogen-free, but also has good flame retardant and heat resistance, less impact strength reduction, and better appearance performance.
[0018] The present invention selects medium-low viscosity polycarbonate, ABS high-rubber powder and ultra-high fluidity acrylonitrile-styrene copolymer to form a high-fluidity matrix. If the viscosity of the polycarbonate is too high and the fluidity is poor, while the viscosity of the acrylonitrile-styrene copolymer is relatively low, the viscosity difference between the two components is large, which easily causes uneven plasticization of the two components. Furthermore, because the system contains a variety of additives with very small addition amounts, the high viscosity of the melt will seriously affect the uniform distribution of the small components in the system, thereby affecting the overall flame retardancy and heat resistance.
[0019] The polycarbonate is preferably at least one of Idemitsu PC FN1900 of Japan, Luxi Chemical PC LXTY1920T, Wanhua PC 2220 and SABIC PC 2200R; the preparation step of the ultra-high flow grade acrylonitrile-styrene copolymer is to heat styrene, acrylonitrile and a small amount of solvent, add initiator and molecular weight regulator to co-polymerize to obtain a polymer, preferably at least one of Swiss INEOS Styrolution AS 2300, LG's AS SA50 and AS 81HF and Zhenjiang Chimei's AS PN-117C; ABS high-rubber powder is a polymer obtained by dissolving butadiene, styrene and acrylonitrile in an organic solvent, heating, adding initiator and molecular weight regulator to carry out graft polymerization, the butadiene rubber content of ABS high-rubber powder is 50-70%, preferably at least one of Kumho's HR181, Taiwan Guoqiao's 60P and Shandong Wanda's WD-132.
[0020] The sulfonate flame retardant in this scheme adopts at least one of potassium benzenesulfonyl sulfonate, potassium perfluorobutyl sulfonate and sodium trichlorobenzene sulfonate. Preferably, the sulfonate flame retardant adopts at least one of FR-2025 of 3M Company of the United States, FR-KSS and STB-FR of Arichem Company of the United States.
[0021] The preparation method of the ultrafine barium sulfate in this scheme is to dissolve the barium salt in water, add it to the sodium hydroxide solution, stir it evenly, add sulfuric acid to react with it, and then precipitate the finished product, wash it, dry it, and then sieve it. The mesh number of the ultrafine barium sulfate of the present invention is 1250 mesh to 5000 mesh, and its purity is more than 98%. Because the mesh number of barium sulfate is too small, its particle size is relatively large, and it is easy to stratify powders with large and small particle sizes when mixed with the powdered components in the formula; if the mesh number of barium sulfate is too large and the particle size is relatively small, its surface energy is large. During the mixing process, some powders are easy to adsorb and agglomerate with each other, resulting in uneven mixing. However, if the purity of barium sulfate is low, the calcium, sodium, phosphorus, sulfur, and lead compounds in its impurities will affect the flame retardant properties and mechanical properties of the alloy material. At least one of H-3000 of Guangzhou Hongtu Mining Company, MY-CDB of Mingyu New Materials Company, and CX-3000 of Shanghai Hongyunyuan Chemical Co., Ltd. is preferred.
[0022] The organic silicon flame retardant in this scheme is prepared by introducing silicon-containing groups into polymer molecular chains using polymerization, grafting and cross-linking techniques. Preferably, at least one of DC-8808 and FCA 107 from Dow Corning of the United States, KR-480 from Shin-Etsu of Japan and FR-3820 from Zhenming Chemical of Dongguan City is used.
[0023] The phosphate flame retardant in this scheme is prepared by a direct thermal method of phosphorus oxychloride with phosphorus chloride and phenol, followed by water washing, alkali neutralization, and concentration of the product, followed by reduced pressure distillation. Preferably, at least one of Zhejiang Wansheng's PX-220, Lanxess's TPP, and Japan Daihachi's PX-200 is used.
[0024] Preferably, the raw material formula further comprises 2-5 parts by weight of a compatible toughening agent, wherein the compatible toughening agent is a core-shell structure toughening agent having an organosilicon-acrylic acid core and methyl methacrylate as a shell.
[0025] The compatible toughening agent with a special core-shell structure used in this scheme has an outer shell of methyl methacrylate that has excellent compatibility with a highly polar matrix, and the inner core of the silicone rubber phase can provide the material with good impact resistance and superior heat resistance. Secondly, the "inner core" serves as a stress concentration point and can induce a large number of silver streaks and shear bands. The generation and interaction of "silver streaks-shear bands" consume a lot of energy, eliminate stress, and prevent external forces from causing permanent damage to the polymer in the PC / ABS alloy material, thereby significantly improving the toughness of the material.
[0026] Preferably, the raw material formula further includes 2-5 parts of polymethyl methacrylate (PMMA for short) by weight, and the melt index of polymethyl methacrylate is 8-16. Specifically, polymethyl methacrylate is at least one of PMMA CM207, PMMA CM211 of Zhenjiang Chimei and PMMA OD10 of Wanhua. The above melt index is conducive to the uniform plasticization of the PMMA component in the melt extrusion of the system to prevent the glossiness of the material surface from being inconsistent. If the melt index of PMMA is too low, it will affect the uniform dispersion of the PMMA component in the system, and if the melt index of PMMA is too high, its molecular weight is small, which will cause a significant decrease in the impact performance of the material.
[0027] After polymethyl methacrylate is blended with the matrix, a metallic gloss is produced on the surface of the PC / ABS alloy material, which greatly improves the gloss of the surface of the PC / ABS alloy material and makes the appearance performance better. It may be due to the unique molecular arrangement structure of polymethyl methacrylate. After mixing with the matrix in this scheme, it does not affect the speed of the light entering the interior when passing through each part, and does not cause the light to scatter in all directions and interfere with each other, which ultimately enables the PC / ABS alloy material to maintain good gloss.
[0028] Preferably, the processing aid includes 0.2-0.3 parts of lubricant, 0.1-0.2 parts of dispersant, 0.2-0.4 parts of antioxidant and 0.5-0.6 parts of anti-dripping agent in parts by weight. The lubricant is pentaerythritol stearate; the dispersant is silicone oil; the anti-dripping agent is a polytetrafluoroethylene polymer; the antioxidant includes a primary antioxidant and an auxiliary antioxidant, the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.
[0029] The lubricant type in this scheme has excellent internal and external lubricity, significantly improves the glossiness of the material, has no obvious weight loss at a high temperature of 320°C, has good thermal stability and low volatility. At least one of Lonza PETS from the United States and PETS-AP from Italy is preferred.
[0030] The dispersant in this solution is preferably dimethyl silicone oil of German Wacker model AK500.
[0031] The anti-dripping agent in this scheme is preferably at least one of K-PT205 of Guangdong Quansheng Chemical, SN3300, SN3201 of Guangzhou Energizer New Materials, and FR-200 of Hananoko.
[0032] The main antioxidant in this scheme is selected from at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol hindered phenol antioxidant and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester, and the auxiliary antioxidant is selected from at least one of tris[2.4-di-tert-butylphenyl] phosphite, tetrakis(2,4-di-tert-butylphenol)-4,4'-biphenyl diphosphite and dilauryl thiodipropionate.
[0033] The present invention also provides a method for preparing a PC / ABS alloy material, comprising the following steps:
[0034] S1: fully and uniformly mixing acrylonitrile-styrene copolymer and ABS high-rubber powder according to the weight ratio of the raw material formula to form an ABS mixture;
[0035] S2: fully and uniformly mixing the ABS mixture with the silicone flame retardant, the sulfonate flame retardant and the superfine barium sulfate to obtain a first mixture, and melt-extruding and granulating the first mixture to obtain a flame retardant masterbatch;
[0036] S3: The flame retardant masterbatch prepared in S2 is fully mixed with other components in the raw material to obtain a second mixed material, and the second mixed material is melt-extruded and granulated to obtain a PC / ABS alloy material.
[0037] In view of the problems that the composite flame retardant system has complex components, large differences in addition ratios, and large differences in particle morphology from the base material, an ABS mixture with good fluidity is first formed, then a flame retardant masterbatch is made with an organosilicon flame retardant, a sulfonate flame retardant and ultrafine barium sulfate, and finally a PC / ABS alloy material is formed by co-blending with a trace amount of phosphate flame retardant, other additives and polycarbonate for extrusion granulation. The masterbatch processing technology of this scheme is used to ensure the flame retardant stability of the material.
[0038] Preferably, in S2, during the melt extrusion stage, the first mixed material is added from the first barrel feeding section of a twin-screw extruder with a length-to-diameter ratio of 40 to 68, and melt extrusion granulation is performed at a rotation speed of 200 to 600 rpm and a temperature of 210 to 230°C; in S3, during the melt extrusion stage, the second mixed material is added from the first barrel feeding section of a twin-screw extruder with a length-to-diameter ratio of 32 to 68, and melt extrusion granulation is performed at a rotation speed of 200 to 600 rpm and a temperature of 230 to 260°C.
[0039] By optimizing the processing conditions of aspect ratio, rotation speed and melting temperature, the material can achieve the advantages of high gloss, high heat resistance, stable impact strength and flame retardant properties.
[0040] Preferably, the raw material formula includes the following components in parts by weight:
[0041] Polycarbonate: 75.8 parts;
[0042] Acrylonitrile-styrene copolymer: 8 parts;
[0043] ABS high glue powder: 3 parts;
[0044] Polymethyl methacrylate: 3 parts;
[0045] Sulfonate flame retardant: 0.2 parts;
[0046] Silicone flame retardant: 2 parts;
[0047] Phosphate flame retardant: 3 parts;
[0048] Superfine barium sulfate: 1 part;
[0049] Compatible toughening agent: 3 parts;
[0050] Lubricant: 0.2 parts;
[0051] Dispersant: 0.1 part;
[0052] Primary antioxidant: 0.1 part;
[0053] Auxiliary antioxidant: 0.1 part;
[0054] Anti-drip agent: 0.5 parts;
[0055] The melt index of polymethyl methacrylate is 8 to 16; the compatible toughening agent is a core-shell structure toughening agent with silicone-acrylic acid as the core and methyl methacrylate as the shell; the lubricant is pentaerythritol stearate; the dispersant is silicone oil; the anti-dripping agent is a polytetrafluoroethylene polymer; the antioxidant includes a main antioxidant and an auxiliary antioxidant, the main antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.
[0056] By further optimizing the raw material formula components and proportions, the flame retardancy of the alloy material can reach V0, the glossiness can reach above 110°, the heat deformation temperature can reach above 105°C, and the impact strength can reach 51.5KJ / m 2 , and all performances are combined to achieve the best. DETAILED DESCRIPTION
[0057] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0058] In the following examples and comparative examples, raw materials, reagents, etc., unless otherwise specified, were obtained from commercial sources, and the same batch of raw materials or reagents were used in the examples and comparative examples.
[0059] The main raw materials and reagents used in the following examples and comparative examples are as follows:
[0060] Polycarbonate PC-1, model K-1300, produced by Teijin, Japan, has a melt index of 3 under the test conditions of 300°C and 1.2KG;
[0061] ABS raw material, model XR-401, produced by LG Chemical in South Korea, has a melt index of 6 under the test conditions of 220℃ and 10KG;
[0062] Polycarbonate PC-2, PC FN1900 model, produced by Idemitsu, Japan, under the test conditions of 300℃ and 1.2KG, the melt index is 19;
[0063] Acrylonitrile-styrene copolymer AS, 81HF model, produced by LG Company of South Korea, under the test conditions of 220℃ and 10KG, the melt index is 60;
[0064] ABS high glue powder, 60P model, produced by Guoqiao factory in Taiwan, China;
[0065] Polymethyl methacrylate, model CM207, produced by Zhenjiang Chimei Factory;
[0066] Phosphate flame retardant, PX-200 model, produced by Japan Dabachi manufacturer;
[0067] Ultrafine barium sulfate, CX-3000 model, produced by Shanghai Hongyunyuan Factory, mesh number is about 3000 mesh;
[0068] Sulfonate flame retardant, FR-KSS model, produced by Arichem, USA;
[0069] Silicone flame retardant, FCA107 model, produced by Dow Corning, USA;
[0070] Compatible toughening agent - a core-shell toughening agent with silicone-acrylic acid as the core and methyl methacrylate as the shell, model S-2100, produced by Mitsubishi Rayon Co., Ltd.
[0071] Lubricant-pentaerythritol stearate, PETS-AP model, produced by an Italian hair base manufacturer;
[0072] Primary antioxidant, model 1076, produced by BASF, Germany;
[0073] Auxiliary antioxidant, model 168, produced by BASF, Germany;
[0074] Dispersant: dimethyl silicone oil, model AK500, produced by Wacker, Germany;
[0075] Anti-drip agent, model SN3300, produced by Guangzhou Entropy Innovation Materials Co., Ltd.
[0076] The raw material compositions of the PC / ABS alloy materials of Examples 1 to 6 are shown in Table 1-1, and the raw material compositions of the PC / ABS alloy materials of Comparative Examples 1 to 5 are shown in Table 1-2.
[0077] For the preparation methods of the PC / ABS alloy materials of Examples 1 to 4 and Comparative Examples 1 to 5, refer to Preparation Item (1); for the preparation methods of the PC / ABS alloy materials of Examples 5 to 6, refer to Preparation Item (2).
[0078] Preparation item (1): A method for preparing a PC / ABS alloy material, comprising the following steps:
[0079] According to the weight of the raw materials, the raw materials were mixed at a speed of 500 rpm for 5 minutes using a high-speed mixer, and melt-extruded and granulated at a temperature of 220° C. to 260° C. using a twin-screw extruder to obtain a PC / ABS alloy material.
[0080] Preparation item (2): A method for preparing a PC / ABS alloy material, comprising the following steps:
[0081] S1: fully mixing acrylonitrile-styrene copolymer and ABS high-rubber powder according to the weight of the raw materials to form an ABS mixture;
[0082] S2: fully mixing the ABS mixture with the silicone flame retardant, the sulfonate flame retardant and the superfine barium sulfate to obtain a first mixture, adding the first mixture to the first barrel feeding section of a twin-screw extruder with an aspect ratio of 40 to 68, and melt-extruding and granulating at a speed of 200 to 600 rpm and a temperature of 210 to 230° C. to obtain a flame retardant masterbatch;
[0083] S3: The flame retardant masterbatch prepared in S2 is fully mixed with other components in the raw material to obtain a second mixed material, and the second mixed material is added to the first barrel feeding section of a twin-screw extruder with a length-to-diameter ratio of 32 to 68, and melt-extruded and granulated at a rotation speed of 200 to 600 rpm and a temperature of 230 to 260°C to obtain a PC / ABS alloy material.
[0084] The performance test corresponding standards are as follows:
[0085]
[0086] Table 1-1 Raw material composition of PC / ABS alloy materials (parts by weight)
[0087]
[0088] Table 1-2 Raw material composition of PC / ABS alloy materials (parts by weight)
[0089]
[0090] From the performance test data in Table 1-1 and Table 1-2, we can conclude that:
[0091] It can be seen from the data of Examples 1 to 2 that the PC / ABS alloy material prepared by the method of the present application has a flame retardant property above V1, a heat resistance heat deformation temperature above 100°C, fewer surface defects, and an impact strength of 40KJ / m 2As described above, in Comparative Example 1, conventional high-content phosphate flame retardant is used in combination with conventional PC / ABS, and the impact strength and heat resistance are significantly reduced, the fluidity is general, and there are many surface defects such as pinholes and pitting in appearance; Comparative Example 1 is compared with Comparative Example 2, and it can be seen that when the high-flow matrix in the present application is used, the surface defects are significantly improved, the fluidity is improved, but the impact performance and heat resistance are not significantly improved; Comparative Example 1 is compared with Comparative Example 3, and it can be seen that when the composite flame retardant system in the present application is used, the heat resistance and impact strength are significantly improved, but due to the lack of a high-flow matrix, the fluidity is general and the flame retardant synergy is not well exerted, so the flame retardant effect is reduced, and due to the diverse components and different forms of the composite flame retardant system, the fluidity is worse, and the surface defects in appearance are more obvious. Comparative Examples 1 to 3 are compared with Example 1. It can be seen that only by using the high-flow matrix and the flame retardant composite system in the present application at the same time can the flame retardant synergy, impact performance, heat resistance and appearance surface defects be achieved at the same time.
[0092] From the comparison between Example 1 and Comparative Examples 4 to 5, it can be seen that when individual flame retardants in the composite flame retardant system are missing, the flame retardant synergistic effect disappears and the flame retardant performance is significantly reduced. It can be seen that the synergistic effect of the composite flame retardant system of the present application depends on the coordination of each component, and although the proportion of phosphate flame retardant in the composite flame retardant system of the present application is small, it can exert an effect equal to or even better than that of a high-content phosphate flame retardant.
[0093] By comparing Example 1 with Example 3, it can be seen that after adding a proper amount of PMMA to the raw material components, the glossiness is significantly improved and the appearance effect is better; by comparing Example 1 with Example 4, it can be seen that after adding a proper amount of a core-shell structure toughening agent with silicone-acrylic acid as the core and methyl methacrylate as the shell to the raw material components, the impact strength and flame retardant properties are significantly improved; by comparing Example 1 with Example 5, it can be seen that the flame retardant stability of the alloy material is improved by introducing the masterbatch processing technology.
[0094] The flame retardant performance of Example 6 reaches V0, the glossiness reaches above 110, the heat deformation temperature is above 105°C, and the impact strength reaches 51.5KJ / m 2 , all the performances are optimal, which is the most preferred embodiment.
[0095] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A PC / ABS alloy material, characterized in that: The raw material formula includes the following components by weight: Polycarbonate: 70-78 parts; Acrylonitrile-styrene copolymer: 8-10 parts; ABS high glue powder: 3-6 parts; Sulfonate flame retardant: 0.2-0.3 parts; Silicone flame retardant: 2-3 parts; Phosphate flame retardant: 3-4 parts; Superfine barium sulfate: 1-3 parts; Processing aids: 1.0-1.5 parts; The polycarbonate has a melt index of 15-25 g / 10 min under the test conditions of 300° C. and 1.2 kg; the acrylonitrile-styrene copolymer has a melt index of 45-60 g / 10 min under the test conditions of 220° C. and 10 kg; The mesh number of the ultrafine barium sulfate is 1250 mesh to 5000 mesh, and the purity is above 98%.
2. The PC / ABS alloy material according to claim 1, characterized in that: The raw material formula further comprises 2-5 parts of a compatible toughening agent in parts by weight, wherein the compatible toughening agent is a core-shell structure toughening agent with organosilicon-acrylic acid as a core and methyl methacrylate as a shell.
3. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The raw material formula further comprises 2-5 parts of polymethyl methacrylate in parts by weight, and the melting index of the polymethyl methacrylate is 8-16 g / 10min.
4. The PC / ABS alloy material according to claim 2, characterized in that: The processing aid includes, by weight, 0.2-0.3 parts of lubricant, 0.1-0.2 parts of dispersant, 0.2-0.4 parts of antioxidant and 0.5-0.6 parts of anti-dripping agent. The lubricant is pentaerythritol stearate; The dispersant is silicone oil; The anti-dripping agent is a polytetrafluoroethylene polymer; The antioxidant comprises a primary antioxidant and an auxiliary antioxidant, wherein the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.
5. The method for preparing the PC / ABS alloy material according to claim 1, characterized in that: The following steps are involved: S1: fully and uniformly mixing acrylonitrile-styrene copolymer and ABS high-rubber powder according to the weight ratio of the raw material formula to form an ABS mixture; S2: fully and uniformly mixing the ABS mixture with the organosilicon flame retardant, the sulfonate flame retardant and the ultrafine barium sulfate to obtain a first mixture, and melt-extruding and granulating the first mixture to obtain a flame retardant masterbatch; S3: The flame retardant masterbatch prepared in S2 is fully mixed with other components in the raw material to obtain a second mixed material, and the second mixed material is melt-extruded and granulated to obtain a PC / ABS alloy material.
6. The method for preparing the PC / ABS alloy material according to claim 5, characterized in that: In S2, in the melt extrusion stage, the first mixed material is added into the first barrel feeding section of a twin-screw extruder with a length-to-diameter ratio of 40 to 68, and melt extrusion granulation is performed at a speed of 200 to 600 rpm and a temperature of 210 to 230° C.; In S3, in the melt extrusion stage, the second mixed material is added from the first barrel feeding section of a twin-screw extruder with an aspect ratio of 32 to 68, and melt extrusion granulation is performed at a rotation speed of 200 to 600 rpm and a temperature of 230 to 260°C.
7. The method for preparing the PC / ABS alloy material according to claim 6, characterized in that: The raw material formula includes the following components by weight: Polycarbonate: 75.8 parts; Acrylonitrile-styrene copolymer: 8 parts; ABS high glue powder: 3 parts; Polymethyl methacrylate: 3 parts; Sulfonate flame retardant: 0.2 parts; Silicone flame retardant: 2 parts; Phosphate flame retardant: 3 parts; Superfine barium sulfate: 1 part; Compatible toughening agent: 3 parts; Lubricant: 0.2 parts; Dispersant: 0.1 part; Primary antioxidant: 0.1 part; Auxiliary antioxidant: 0.1 part; Anti-drip agent: 0.5 parts; The melt index of the polymethyl methacrylate is 8 to 16 g / 10 min; The compatible toughening agent is a core-shell structure toughening agent with organosilicon-acrylic acid as the core and methyl methacrylate as the shell; The lubricant is pentaerythritol stearate; The dispersant is silicone oil; The anti-dripping agent is a polytetrafluoroethylene polymer; The antioxidant comprises a primary antioxidant and an auxiliary antioxidant, wherein the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.
Citation Information
Patent Citations
High gloss, high hardness and uvioresistant polycarbonate plastic alloy
CN101469121A
Solvent-resistant halogen-free flame-retardant PC / PETG alloy and preparation method thereof
CN114213827A
Flame-resistant thermoplastic moulding material
CN1341140A